OPTIMIZATION OF SIMPLY SUPPORTED CASTELLATED I-BEAMS LOADED BY A UNIFORMLY DISTRIBUTED LOAD - Oleg Goryachevskiy (International Journal for Computational Civil and Structural Engineering, 2019)
The paper discusses the problem of optimizing the geometric parameters of simply supported I-beams in order to maximize their load carrying capacity. Numerical simulation of various types of failure of castellated I- beams with ideal elastic-plastic steel is carried out. The stability of the wall, the strength of the welds and flanges, depending on the geometric parameters investigated. Using the coordinate descent method, the optimization problem is solved for nine design schemes with respect to the section height and the weld length. It was revealed that in short beams the section height should be less and the weld length longer, in contrast to long beams.